Migrainous vertigo - Martins, João (2011)
Migrainous vertigo, assumed to be a migraine vestibular symptom, is a heterogeneous clinical entity which typically presents as recurrent vertigo attacks. Diagnosis is made with a careful history and examination and a high index of suspicion. It should be considered in the differential diagnosis of recurrent vertigo syndromes. Treatment recommendations are based on trigger identification and avoidance, and prophylactic migraine medications.The authors report a case of a 43-year-old woman, with history of migraine headaches, and a prolonged history of recurrent rotational vertigo attacks, provoked or exacerbated by identifiable triggers and accompanied by other somatosensorial symptoms. The patient was effectively treated with trigger avoidance and migraine prophylactic medication.